Psychological intervention plan to favor psychosocial factors in the female youth softball team (Original) (Revista científica Olimpia, 2020)
The sports team in his dynamics represents the characteristics of a group partner psychological, organized in sports, you introduce of whom fundamental you are to raise his qualitative and quantitative performance in the course of workout stops after to reflect it in the competition. The fact that the challenge to design complete plans of much more intervention in the collective sports, once the need to raise the group efficiency in order that the team may act as a whole and I eat group was given partner psychological imposes itself is that's why he must be I object of intervention these characteristics for the better partner psychological.Alfredo Utset Bertot for the sake of applying a plan of psychological intervention that favor the development the team's psychosocial accomplished this investigation himself in Softball youthful female team of the U.D.D and for there in a bigger group efficiency. Partner métric utilized fact-finding methods of the theoretic knowledge, empiricist and techniques themselves. Partner psychological made suitable in the team, the adjusting of the goals highlight like results to favor climates themselves so much individual like group, a notable improvement in regards to the group communication was obtained and they lifted the group cohesion's indicators in the second diagnosis with very positive results. Softball youthful female team obtained the 1er place in the National Games improving his acting of a 2do place in give them the prior year, that constitutes a practical contribution for development psychosocial in sports teams specifically in the sports with ball.
Keywords: sports team; factors psycho social; development partner psychological; group efficiency; softball youthful female; plan of psychological intervention